2010
DOI: 10.1016/s1470-2045(10)70054-1
|View full text |Cite
|
Sign up to set email alerts
|

Effect of zoledronic acid on disseminated tumour cells in women with locally advanced breast cancer: an open label, randomised, phase 2 trial

Abstract: Summary Background Treatment with bisphosphonates decreases bone loss and can increase disease-free survival in patients with breast cancer. The aim of our study was to assess the effect of zoledronic acid on clearance of disseminated tumour cells (DTCs) from the bone marrow in women undergoing neoadjuvant chemotherapy for breast cancer. Methods Patients were recruited for this open-label, phase 2 randomised trial between March 17, 2003, and May 19, 2006, at a single centre. Eligible patients had clinical s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
170
0
5

Year Published

2011
2011
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 256 publications
(184 citation statements)
references
References 39 publications
9
170
0
5
Order By: Relevance
“…Based on the rationale that ZA may interfere with stimulatory interactions between the bone microenvironment and tumor cells and on observations of direct antiproliferative effects against tumor cells (3)(4)(5), the drug was also evaluated for the treatment of primary and metastatic bone tumors. As expected, ZA demonstrated clinical antitumor activity in multiple myeloma (6) and osteosarcoma (7) and against (micro)metastatic bone and/or bone marrow disease in solid tumors (8,9). In preclinical studies in Ewing sarcoma, ZA was found to inhibit in vivo tumor growth both alone and in synergism with chemotherapies (4,5), and initial clinical reports suggest that ZA combined with chemotherapy may be effective in refractory disease (10).…”
Section: Introductionmentioning
confidence: 63%
See 1 more Smart Citation
“…Based on the rationale that ZA may interfere with stimulatory interactions between the bone microenvironment and tumor cells and on observations of direct antiproliferative effects against tumor cells (3)(4)(5), the drug was also evaluated for the treatment of primary and metastatic bone tumors. As expected, ZA demonstrated clinical antitumor activity in multiple myeloma (6) and osteosarcoma (7) and against (micro)metastatic bone and/or bone marrow disease in solid tumors (8,9). In preclinical studies in Ewing sarcoma, ZA was found to inhibit in vivo tumor growth both alone and in synergism with chemotherapies (4,5), and initial clinical reports suggest that ZA combined with chemotherapy may be effective in refractory disease (10).…”
Section: Introductionmentioning
confidence: 63%
“…ZA has attracted recent interest as a non-cytotoxic anticancer drug and is under clinical investigation for use in various diseases, including primary bone tumors (3,4,(7)(8)(9). Promising features of ZA include the observed anticancer synergies between bisphosphonates and cytotoxic chemotherapies (4,30), the favorable toxicity profile, and the proposed effect on the tumor-promoting bone/bone marrow microenvironment to prevent dissemination.…”
Section: Discussionmentioning
confidence: 99%
“…2,3,[13][14][15][16][17] Recently, preclinical and clinical data have also demonstrated anticancer effects of bisphosphonates in breast and other cancer types. [18][19][20][21][22][23][24][25][26][27][28][29][30][31][32] The prevention and treatment of bone loss with upfront (initiated simultaneously with letrozole) versus delayed (initiated with a decrease in T score to <À2 or occurrence of clinical nontraumatic fracture) zoledronic acid in early breast cancer patients receiving letrozole was evaluated in 3 similarly designed, geographically diverse studies (Z-FAST; ZO-FAST; E-ZO-FAST) and in the similarly-designed N03CC study. 15 Interim (<36 months follow-up) results from the former 3 studies indicate that upfront rather than delayed-start zoledronic acid is significantly more effective in preventing bone loss.…”
Section: Introductionmentioning
confidence: 99%
“…Bisphosphonate is able to protect against resorption of the bone by downregulating the function of osteoclasts (29), preventing cancer cell activation by reducing cytokine release from the bone marrow and resulting in protection against skeletal bone events (30). Recent studies have also demonstrated the possible impact of bisphosphonates in protecting against bone metastasis in breast cancer patients (31). Experimental evidence shows that humanized monoclonal antibody against PTHrP suppresses osteolytic bone metastasis of human breast cancer cells (32).…”
Section: Bone Metastasis (Bm) P-value Factors At the ----------------mentioning
confidence: 99%